Bahasa Indonesia - Agustine, Daniar Arisandi Dwi; Hakimah, Nurul; Nurmayanti, Rani (NUTRITURE JOURNAL; Vol 2 No 3 (2023): Nutriture JournalDO - 10.31290/nj.v3i2.4102, 2023)
Background: Food that is not safe will be vulnerable to contamination from chemical, biological, and physical hazards. Food poisoning can be prevented by implementing the “Five Keys to Safer Food”. Food handlers who have low knowledge and attitudes towards food safety have 2,167 times risk of making their processed food unsafe. Food safety education is useful for adding insight into food handlers, they can implement in their work to improve quality and consumer confidence. Objective: The purpose of this study was to determine the knowledge level and attitudes toward food safety for food handlers at Pondok Sawah Catering Turen before and after being given education. Design: This research uses descriptive quantitative. The research population was 13 people. The sampling technique used purposive sampling and obtained 13 people. Results: There was a change in knowledge of food handlers with the highest increase based on characteristic, adult (31%), junior high school education level (38%), working period ? 3 years (31%), and female (46%). There was a change in the attitudes of food handlers with the highest increase based on the characteristic, adult (31%), high school education level (23%), working period < 3 years (31%), and female (38%) after provided food safety education.   Conclusions: There was a change in the knowledge levels and attitudes of food handlers after provided food safety education.